How political actors use the media : a functional analysis of the media's role in politics - Aelst, Peter van ; Walgrave, Stefaan,1966- (Palgrave Macmillan, 2020)
This book investigates how individual politicians and political parties strategically make use of the media to reach their political goals. Looking beyond a purely Americentric viewpoint, the chapters present data from more than ten Western democracies to argue that the media are both a source of information and an arena for political communication. This double functional role of the media is examined from both a theoretical and an empirical perspective, including chapters dealing with different aspects of politics - from campaigning to law making - and within different political contexts. The role of the news media is discussed from the perspective of the political actor, focusing on both the opportunities and the constraints the news media provide, resulting in a multidisciplinary text that will appeal to students and scholars of both communication and political science. Information and arena : the dual function of the news media for political elites / Peter Van Aelst and Stefaan Walgrave -- An intervening intermediary : making political sense of media influence / Gunnar Thesen -- Celebrities as political actors and entertainment as political media / Regina G. Lawrence and Amber E. Boydstun -- Political public relations and mediatization : the strategies of news management / Jesper Strömbäck and Frank Esser -- Too powerful or just doing their job? : explaining differences in conceptions of media power among politicians and journalists / Rens Vliegenthart and Morten Skovsgaard -- What politicians learn from the mass media and why they react to it : evidence from elite interviews / Julie Sevenans -- The media independency of political elites / Stefaan Walgrave, Julie Sevenans, Alon Zoizner, and Matthew Ayling -- When politicians react to the media : how the attitudes and goals of political elites moderate the effect of the media on the political agenda / Alon Zoizner, Yair Fogel-Dror, and Tamir Sheafer -- Moving beyond the single mediated arena model : media uses and influences across three arenas / Aeron Davis -- The charm of salient issues? : parties' strategic behavior in press releases / Caroline Dalmus, Regula Hänggli, and Laurent Bernhard -- News tone and the government in the news : when and why do government actors appear in the news? / Christoffer Green-Pedersen, Peter B. Mortensen, and Gunnar Thesen -- Why do politicians use the media when making laws? : a study on the functional use of mass media during legislative processes / Lotte Melenhorst and Peter Van Aelst -- Information source and political arena : how actors from inside and outside politics use the media / Nayla Fawzi -- Elaborating and specifying the information and arena framework / Stefaan Walgrave and Peter Van Aelst.